The Effects of Sports Activities on Adolescents' Socioemotional Development - Kirana, Garda Sukma; Zahra, Ilmi Fauziyyah; Aisyah, Adinda Nur; Swastika, Diani; Putri, Nadia Ikhsani; Noveni, Nia Anggri (PSIMPHONI, 2023)
During adolescence, whose experiencing identity crisis, they do a lot of exploration in various activities, including sports. This study aims to determine the effect of sports activities on socioemotional development. The subjects of this study were adolescents aged 12-22 years using sampling technique purposive sampling. The method used in this research is descriptive qualitative. The analyze data technique in this research is qualitative approach technique using google form questionnaire survey. The results of this study are 1) identity crisis characterized by seeking standards for exercise; 2) there are 13 participants who found career goals in the field of sports, which means that they have passed a period of identity crisis; 3) there are 155 participants exercise because they influenced by group, not their parents or self-awareness; 4) the self-standardization period proven by setting standards in sports; 5) among 212 participants, 134 of them have not found self-standardization when target has been achieved; 6) among 212 participants, 193 of them stated that they have more stable emotions after exercising. Exercising is one of the explorations that teenagers can do to get through the identity crisis. Some participants were able to get through the identity crisis by exercising and some had to do further exploration.